Electron energy-loss spectra of graphene oxide for the determination of oxygen functionalities. (November 2015) - D'Angelo, D.; Bongiorno, C.; Amato, M.; Deretzis, I.; La Magna, A.; Compagnini, G.; Spanò, S.F.; Scalese, S.
Abstract: Graphene based materials for large-scale production can be obtained starting from graphene oxide (GO) by means of suitable treatments in order to reduce the number of oxygen functional groups. The composition and the structure of GO and reduced GO depend on the synthesis and reduction methodologies. In this work, GO was prepared by a modified Hummers method and reduced by pulsed laser irradiation using visible wavelength (532 nm). Transmission electron microscopy analyses were performed and dual electron energy-loss spectra were acquired in different regions of GO and reduced GO flakes. Experimental results show a series of characteristic peaks related to C and O K-edge shells. Density functional theory calculations of the high-loss region of the electron energy loss spectra at atomic level enable a reliable correlation between the observed experimental peaks to the presence of different oxygen functional groups on the graphene surface and the corresponding atomic configurations.